Image processing based human detection and social distancing measurements with monitoring via fine tuned deep learning and computer vision - Datta, Anurag; Fatema, Kaniz; Tasnim, Nowshin; Sitara, Faria; Das, Mrithik Kanti (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.